Effect of ascorbic acid concentrations on hemodynamics and inflammation following lyophilized plasma transfusion. Issue 1 (July 2015) - McCully, Sean P.; Martin, David T.; Cook, Mackenzie R.; Gordon, Nicole T.; McCully, Belinda H.; Lee, Tim H.; Dean, Rondi K.; Rick, Elizabeth A.; Moren, Alexis M.; Fair, Kelly A.; Undurraga, Vicente J.; Watson, Kathrine M.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Compared with lyophilized plasma (LP) buffered with other acids, LP with ascorbic acid (AA) attenuates systemic inflammation and DNA damage in a combat relevant polytrauma swine model. We hypothesize that increasing concentrations of AA in transfused LP will be safe, will be hemodynamically well tolerated, and will attenuate systemic inflammation following polytraumatic injury and hemorrhage in swine. METHODS This prospective, randomized, blinded study involved 52 female swine. Forty animals were subjected to our validated polytrauma model and resuscitated with LP. Baseline control sham (n = 6), operative control sham (n = 6), low-AA (n = 10), medium-AA (n = 10), high-AA (n = 10) groups, and a hydrochloric acid control (HCL, n = 10) were randomized. Hemodynamics, thrombelastography, and blood chemistries were assessed. Inflammatory cytokines (tumor necrosis factor α, interleukin 6 [IL-6], C-reactive protein, and IL-10) and DNA damage were measured at baseline, 2 hours, and 4 hours after liver injury. Significance was set at p < 0.05, with a Bonferroni correction for multiple comparisons. RESULTS Hemodynamics, shock, and blood loss were similar between groups. All animals had robust procoagulant activity 2 hours following liver injury. Inflammation was similar between groups at baseline, and AA groups remained similar to HCL following liver injury. IL-6 and tumor necrosis factor α were increased at 2 hours and 4 hours compared with baseline within all groups (p < 0.008). DNA damage increased at 2 hours compared with baseline in all groups (p < 0.017) and further increased at 4 hours compared with baseline in HCL, low-, and high-AA groups (p < 0.005). C-reactive protein was similar between and within groups. IL-10 increased at 2 hours compared with baseline in low- and high-AA groups and remained elevated at 4 hours compared with baseline in the low-AA group (all, p < 0.017). CONCLUSION Concentrations of AA were well tolerated and did not diminish the procoagulant activity of LP. Within our tested range of concentrations, AA can safely be used to buffer LP.